Cooperation of interDisciplinary in vocational education interior architecture design studio study case - Tosun, Vehbi; Akbaş, Gamze; Erdemir, Zuhal; ERÇETİN, ARZU (My University, 2020)
Interdisciplinary collaborative teaching and learning methods on national and international academic platforms is the agenda of discussion environments in recent years. In particular, the key role of the interior design studios' educational environment, which constitutes the backbone of interior architecture education, is to play a key role in providing students with interdisciplinary design understanding and teamwork skills.Because studio studies are basically the courses in which all the vocational education taken are reinforced, developed and the design product is put forward. It is possible to consider the historical background of the main themes found in cun-ent studio education discussions within the framework of an ongoing change process since the 1950s.Especially, the Bauhaus education model of Turkey in the acceptance, training with the shaping of studio work in this context, from the art to technique, a lot of discipline has emerged at the same time expressing the difference. The aim of this article is to draw a holistic picture by considering the subject of interdisciplinary collaborative design in a historical perspective in architectural / interior design education which is widely available in the literature today. Such a picture, in the field of higher education in our country, within the framework of Bologna reform, experienced a change process and general competencies expected to gain a balanced education of interior architecture and in these days, where occupational-specific competences are identified, it is thought to increase awareness.
Keywords: Interior Architecture Education; Design Studio Studies; Interdisciplinary Study; Vocational Education; İç Mimarlık Eğitimi; Tasarım Stüdyosu Çalışmaları; Disiplinlerarası Çalışma; Mesleki Eğitim